FOURSQUARE IN ENGLISH EXPOSITORY TEXT CONSTRUCTION - Yunita Hening (Universitas Bandar Lampung, 2019)
This research proposes a method, namely four-square that the teachers can implement as scaffolding in teaching English as Foreign Language (EFL) writing. The introduction of four-square, mainly aims at the learners’ ability in creating written texts which are grammatically accurate and functional in social context. It is because this method might help the learners to construct a good text and to realize their linguistic mistakes in writing. The significant characteristic of four-square to the development of learners’ writing skill is the fact that it applies the process and genre approaches at the same time. In four-square, the learners consider the steps of writing; brainstorming the idea, prewriting, organizing, writing first draft, revising draft, and producing the final writing. In conclusion, four-square is a scaffolding in writing which might bring the learners to the sufficient and effective path of writing process.